CYTOTOXICITY OF SEED KERNEL WATER EXTRACT OF CAESALPINIA BONDUC (L) ROXB. ON ROOT MERISTEM CELLS OF ALLIUM CEPA L. - LODH , DEBASREE; R. K. SINHA (The Bioscan, 2013)
Cytotoxicity of seed kernel water extracts of Caesalpinia bonduc (L) Roxb. was studied in root meristem cells of Allium cepa L. The root tips of A. cepa were treated with different concentrations (0.05%, 0.1%, 0.25%, 0.5%, 1%) of crude extract for 4h, 6h, 8 h, 12h, 24h and 48h along with control. All the concentrations of water extracts treatment significantly decreased the mitotic index compared to control in all concentrations of treatments. Cytological effects included various levels of metaphase arrest along with clumping tendency of chromosomes. Selective concentrations (0.05%, 0.1% and 1%) of treatment also produced pre-treatment effects with well spread and condensed metaphase chromosomes. Infrequent incidence of unequal separation of chromosomes at anaphase was also observed. Recovery experiment clearly suggests that the present mito-inhibition and metaphase arrest are temporary and recovered within 24 h of incubation.